Comparative genomics of small RNA regulatory pathway components in vector mosquitoes - Foy Brian D; Hess Ann M; Black William C; Campbell Corey L (BMC Genomics, 2008)
Abstract Background Small RNA regulatory pathways (SRRPs) control key aspects of development and anti-viral defense in metazoans. Members of the Argonaute family of catalytic enzymes degrade target RNAs in each of these pathways. SRRPs include the microRNA, small interfering RNA (siRNA) and PIWI-type gene silencing pathways. Mosquitoes generate viral siRNAs when infected with RNA arboviruses. However, in some mosquitoes, arboviruses survive antiviral RNA interference (RNAi) and are transmitted via mosquito bite to a subsequent host. Increased knowledge of these pathways and functional components should increase understanding of the limitations of anti-viral defense in vector mosquitoes. To do this, we compared the genomic structure of SRRP components across three mosquito species and three major small RNA pathways. Results The Ae. aegypti, An. gambiae and Cx. pipiens genomes encode putative orthologs for all major components of the miRNA, siRNA, and piRNA pathways. Ae. aegypti and Cx. pipiens have undergone expansion of Argonaute and PIWI subfamily genes. Phylogenetic analyses were performed for these protein families. In addition, sequence pattern recognition algorithms MEME, MDScan and Weeder were used to identify upstream regulatory motifs for all SRRP components. Statistical analyses confirmed enrichment of species-specific and pathway-specific cis-elements over the rest of the genome. Conclusion Analysis of Argonaute and PIWI subfamily genes suggests that the small regulatory RNA pathways of the major arbovirus vectors, Ae. aegypti and Cx. pipiens, are evolving faster than those of the malaria vector An. gambiae and D. melanogaster. Further, protein and genomic features suggest functional differences between subclasses of PIWI proteins and provide a basis for future analyses. Common UCR elements among SRRP components indicate that 1) key components from the miRNA, siRNA, and piRNA pathways contain NF-kappaB-related and Broad complex transcription factor binding sites, 2) purifying selection has occurred to maintain common pathway-specific elements across mosquito species and 3) species-specific differences in upstream elements suggest that there may be differences in regulatory control among mosquito species. Implications for arbovirus vector competence in mosquitoes are discussed.